Not sure if this is the correct place to post this.(adsbygoogle = window.adsbygoogle || []).push({});

dy/dt = 0, find y(t)

My professor told me that the chain rule is used to determine that (dy/dt)*dt = dy, but I just don't see it.

Multiply both sides by dt.

(dy/dt)*dt = 0dt

(dy/dt)*dt = 0

dy = 0, then integrating both sides:

y = C

dy/dt is the derivative of the function y in respect to t, and dt is just a small change in t. How is the chain rule used here? dz/dx = dz/dy * dy/dx makes a lot more sense to me, but I just don't see that here.

**Physics Forums - The Fusion of Science and Community**

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Chain rule

Loading...

Similar Threads - Chain rule | Date |
---|---|

I Chain rule found in MIT video | Jul 14, 2016 |

Chain rule | Feb 10, 2014 |

Check whether I am correct in Chain Rule | Oct 29, 2013 |

The chain rule (PDE) | Feb 8, 2012 |

Chain rule for implicit differentiation | Jan 21, 2012 |

**Physics Forums - The Fusion of Science and Community**